Relationship Between Emotional Intelligence and Fear of Performance Failure Among University Undergraduates in Southeast, Nigeria (Journal of Guidance and Counselling Studies, 2024)
This study examined the relationship between emotional intelligence and fear of performance failure among university undergraduates. Five research questions were answered with five corresponding null hypotheses formulated and tested at 0.05 significance level. The study adopted the correlational research design. One thousand, one hundred and fifty second year undergraduates were used in the study. Two sets of questionnaires ‘Emotional Intelligence Questionnaire (EIQ)’ and ‘Fear of Performance Failure Questionnaire (FOPFQ)’ were used for data collection while the reliability of the instruments were established using Cronbach’s alpha method and the alpha co-efficient gotten were 0.74 for EIQ and 0.78 for FOPFQ. The findings of the study revealed that the components of emotional intelligence have low positive relationship with fear of performance failure among university undergraduates. The null hypotheses were also rejected since emotional intelligence cannot be entirely neglected in seeking to address undergraduates fear of performance failure. This implies that the influence of emotional intelligence on fear of performance failure is significant enough to be valuable for students’ progress. Based on the findings of the study, it was recommended that lecturers should ensure during instructional delivery to intimate university undergraduates on the need to train themselves and imbibe emotional intelligence. This will go a long way to help them to conquer fear of performance failure. It was also recommended that during orientation programmes, the university administration should try their best to intimate undergraduates on the need not to see examinations as a do or die affair. They should be encouraged to give maximum effort and should be rewarded when they accomplish it.
Keywords: Emotional Intelligence; Fear of Performance Failure; Mood Regulation; Self-Awareness; Internal Motivation; Interpersonal Skill; Empathy Response